Keeping Hold of the Jewel: Buddhist Youth Activism and Multidirectional Migration in Mountain Java - Rizzo, Roberto (Annali di Ca’ Foscari: Serie Orientale)
The paper investigates the emergence of a youth organisation in rural Central Java and its relevance for the channelling of Buddhist revivalist stances in the Temanggung area. Buddhism was introduced in the Muslim-majority regency in the 1950s through the lens of “revival”. However, in recent decades, local institutional and noninstitutional Buddhist actors have framed oftentimes the religious demographics as well as attendance to formal religious worship as being in a long-term state of decadence and abandonment, particularly on the side of young residents. Many Buddhists perceive this to be to the advantage of either other formal religious affiliations (Islam, Christianity) or a more generalised trend of indifference towards communal forms of religious engagement. The article follows the formation of the revivalist group, Pemuda Buddhis (the “Buddhist Youth”) in the Temanggung highlands and the social-cultural ramifications that converge in its origination, practices and agenda. Rather than instantiating a linear “return”, the Buddhist revitalisation efforts promoted by the group materialise, in fact, a novel religious scenario, marked by a sharper influence of Theravāda Buddhism and, on the other hand, a mélange of ethnocultural and Javanese-identitarian stances. More specifically, the paper intends to show how the formation of the youth organisation and the on-the-ground activities implemented reflect wider dynamics of internal mobility as well as new economic/entrepreneurial sensibilities.